A sustainable energy management soft computing system for photovoltaic/wind hybrid power generation system. (9th July 2019) - Selvam, R.; Velavan, R.; Soundarrajan, A.
Recently, renewable energy sources turned all attentions and became more attractive, due to increasing energy needs and factors like limited reserves, increasing energy costs and environmental pollution. As these sources do not cause any environmental pollution and have an unlimited supply, it is extensively utilised every day. Solar and wind are the two renewable sources considered in this paper. The renewable sources like solar and wind power are established to test the system. The development of this system fulfils the power demand, since solar and wind are not reliable with regard to quality power and sustainability. Depending upon the availability of those power sources, the extra power demand is provided from either PV or wind source. The whole system is operated using adaptive transformational optimisation (ATOA) method. The proposed energy management system has been validated through simulation and the result obtained will prove the effectiveness of proposed system.